Use of sargassum polycystum as a prebiotic agent - Shamsudin, Mariana Nor; Md. Yussof, Fatimah; Mohammed Aliyu-Paiko,; Nazarudin, Muhammad Farhan; Zakaria, Md. Shater (2013)
The present invention discloses the use of Sargassum polycystum as a prebiotic agent. Accordingly, the present invention provides feed compositions or pharmaceutical compositions with prebiotic function, which comprise Sargassum polycystum in an amount of 1-3% by weight, as well as preparation methods thereof.